An optimized ore blending method based on the consolidation capacity of coarse-grained iron ore

CN120766808BActive Publication Date: 2026-11-03HANDAN IRON & STEEL GROUP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510801340.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-16
Publication Date
2026-11-03
Estimated Expiration
2045-06-16

AI Technical Summary

Technical Problem

Existing methods for evaluating the sintering performance of iron ore fail to accurately reflect the kinetic differences of coarse-grained iron ore powder during the sintering process, making it impossible to establish an effective relationship between the sintering performance and the actual performance of iron ore.

Method used

By measuring the consolidation strength and pulverization rate of various coarse-grained iron ore varieties, and combining the core ore composition and raw material structure, the overall consolidation strength and pulverization rate are calculated, the sintering blending scheme is optimized, and the correspondence between iron ore sintering performance and actual production quality indicators is established.

Benefits of technology

This has enabled quantitative evaluation of sinter quality indicators, optimized sinter blending structure, improved resource utilization efficiency, and promoted the sustainable development and economic benefits of steel enterprises.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses an optimization ore blending method based on coarse particle iron ore consolidation capacity, comprising the following steps: 1) taking the scheme before adjustment as a benchmark ore blending scheme, and taking the scheme after adjustment as a tentative adjustment ore blending scheme; 2) measuring the consolidation capacity of the coarse particle iron ore in the benchmark ore blending scheme according to the raw material structure of the scheme, and respectively measuring the consolidation strength and the pulverization rate of each kind of coarse particle iron ore; measuring the consolidation capacity of the coarse particle iron ore in the tentative adjustment ore blending scheme according to the raw material structure of the scheme, and respectively measuring the consolidation strength and the pulverization rate of each kind of coarse particle iron ore; 3) calculating the mass fraction Q of the core ore in the mixed material of each scheme 核 ; and calculating the content A of the raw material in the core ore of each scheme i . The application has the advantages of simple operation process, strong practicability, adaptability to diversified raw material structure, and the like, can establish a fast and accurate iron ore sintering performance evaluation and ore blending structure optimization method for enterprises, and realizes reasonable utilization of resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sintering batching technology, and in particular to an optimized ore blending method based on the consolidation capacity of coarse-grained iron ore. Background Technology

[0002] Establishing rapid and accurate methods for evaluating iron ore sintering performance and optimizing sintering blends is of great practical significance for guiding enterprises in ore procurement, optimizing blends, and adjusting sintering processes.

[0003] Iron ore sintering is a process in which iron ore powder, flux, and fuel are mixed in a certain proportion, with an appropriate amount of water added, and then granulated and sintered into blocks at high temperature on a sintering trolley. Different particle sizes of iron ore powder behave and play different roles in the granulation and sintering processes. The mixture of fine-grained iron ore powder and flux, under the influence of water, forms adhesive powder that adheres to the coarse-grained core ore, forming quasi-particles that constitute the basic units of the sintered material. Under high temperature, these basic units first undergo a solid-phase reaction with the iron phase and CaO in the adhesive powder to form low-melting-point minerals, followed by the formation of a liquid phase. As the temperature gradually increases, the amount of liquid phase increases, the fluidity improves, and the penetration ability into the core ore gradually strengthens. Due to differences in density and loss on ignition value, the core ores exhibit different behaviors during liquid-phase infiltration. Hematite, being relatively dense, leaves a more intact unreacted core after interaction with the liquid phase, while the reaction zone in the middle is thinner. Limonite, on the other hand, retains numerous pores after the evaporation of crystal water, readily absorbing the liquid phase and undergoing interaction reactions; its unreacted cores are smaller, and the reaction zone is thicker. Therefore, from the perspective of basic units, the consolidation strength of sintered ore should consist of three parts: 1. The strength of the binder phase after the initial interaction between the liquid phase and the core ore reaches equilibrium; 2. The strength of the interaction reaction zone between the initial liquid phase and the core ore; 3. The strength of the unreacted cores.

[0004] While existing methods for evaluating the sintering performance of iron ore have conducted in-depth studies on different sintering behaviors of iron ore, they have failed to establish an accurate and reliable relationship between these methods and the actual sintering performance of iron ore. The main reason is that some high-temperature characteristic evaluation methods oversimplify the sintering system and ignore the influence of the kinetic differences in the particle size composition of iron ore during the sintering process. Currently, coarse-grained iron ore powder accounts for more than 60% of the sintering raw materials in domestic steel enterprises, and the proportion of particles larger than 0.5 mm in each coarse-grained iron ore powder is on average over 70%. Therefore, coarse particles constitute the vast majority of the sintered material. Studying the interaction and reaction behavior between coarse-grained iron ore and the sintering liquid phase is more helpful in revealing the intrinsic connection between the basic properties of iron ore and its sintering performance. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide an optimized ore blending method based on the consolidation capacity of coarse-grained iron ore that can predict sintering performance.

[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention includes the following steps: 1) taking the original ore blending scheme as the benchmark ore blending scheme and the ore blending scheme to be adjusted as the ore blending scheme to be adjusted;

[0007] 2) Based on the raw material structure of the benchmark blending scheme, the consolidation capacity of the coarse-grained iron ore in the scheme was measured, and the consolidation strength and pulverization rate of each type of coarse-grained iron ore were measured respectively; based on the raw material structure of the proposed adjusted blending scheme, the consolidation capacity of the coarse-grained iron ore in the scheme was measured, and the consolidation strength and pulverization rate of each type of coarse-grained iron ore were measured respectively.

[0008] 3) According to the proportions B of each raw material in the benchmark ore blending scheme and the proposed adjusted ore blending scheme respectively. i The content of P in each raw material ore i Calculate the mass fraction Q of the nuclear ore in the blended material of each scheme. 核 The calculation formula is as follows (Ⅰ); then, according to the proportions B of each raw material in the benchmark ore blending scheme and the proposed adjusted ore blending scheme, respectively. i The content of P in each raw material ore 核i Calculate the content A of this raw material in the nuclear ore of each scheme. i The calculation formula is as follows (II):

[0009] Q 核 =∑P i ×B i , ∑B i =1 (Ⅰ);

[0010] A i =P 核i ×B i / Q 核 , ∑A i =1 (Ⅱ);

[0011] 4) Calculate the overall consolidation strength and overall pulverization rate of the raw material structure in the benchmark ore blending scheme and the raw material structure in the proposed adjusted ore blending scheme, respectively. The calculation formulas are as follows: (III) and (IV):

[0012] Overall consolidation strength = ∑G i ×A i (III);

[0013] Overall pulverization rate = ∑F i ×A i (Ⅳ);

[0014] 5) Taking into account the differences in the overall consolidation strength and overall pulverization rate between the raw material structure of the benchmark ore blending scheme and the raw material structure of the proposed adjusted ore blending scheme, determine or readjust the ore blending structure.

[0015] Furthermore, the coarse-grained iron ore is an iron ore variety containing particles of ≥0.5mm size.

[0016] The beneficial effects of adopting the above technical solution are as follows: This invention simulates the chemical composition of the adhesive powder, determines the consolidation strength and pulverization rate of various types of coarse-grained iron ore, and performs theoretical calculations based on the core particle composition of the raw material structure to predict the sintering performance of the raw material structure, thereby optimizing the sintering ore blending.

[0017] The overall consolidation strength and pulverization rate of the ore blending structure obtained by this invention comprehensively consider the composition of the core ore and the contribution of different types of core ore to the strength and yield. It can effectively reflect the correspondence between the sintering performance of a single type of iron ore and the overall performance of the ore blending structure, thereby achieving quantitative evaluation of sinter quality indicators. This invention is simple to operate, highly practical, and adaptable to diverse raw material structures. Under the current conditions of scarce high-quality iron ore resources, it can provide enterprises with a rapid and accurate method for evaluating iron ore sintering performance and optimizing ore blending structures, achieving rational resource utilization. It has a positive and significant effect on promoting the sustainable development of steel enterprises and improving economic efficiency, and has strong promotion and application value. Detailed Implementation

[0018] The present invention will now be described in further detail with reference to specific embodiments.

[0019] The inventors discovered in their research that there is a good fit between the strength of sintered ore under different sintering raw material structure conditions and the weighted average calculated value of the core ore composition and core ore consolidation strength of the raw material structure. Based on this, a correspondence between the sintering performance of iron ore and the actual production quality indicators can be established, providing technical support for enterprises to optimize sintering ore blending and guide iron ore procurement.

[0020] This optimized ore blending method based on the consolidation capacity of coarse-grained iron ore includes the following steps:

[0021] 1) Adjustment of sintering ore blending scheme: Based on the ore blending scheme that the enterprise has been operating stably for a long time, the sintering ore blending scheme is to be adjusted according to the enterprise's own resource situation and resource adjustment plan, and the proposed adjustment ore blending scheme is determined.

[0022] 2) Determination of iron ore consolidation capacity:

[0023] 2.1) Based on the raw material structure of the benchmark ore blending scheme, the consolidation capacity of the coarse-grained iron ore in the scheme was determined, and the consolidation strength and pulverization rate of each type of coarse-grained iron ore were measured respectively.

[0024] 2.2) Based on the raw material structure of the proposed ore blending scheme, the consolidation capacity of the coarse-grained iron ore in the scheme was measured, and the consolidation strength and pulverization rate of each type of coarse-grained iron ore were measured respectively; the coarse-grained iron ore is an iron ore variety containing particles ≥0.5mm, such as Baka powder, Newman powder, etc.

[0025] The determination process for the consolidation strength and pulverization rate is as follows:

[0026] A) Take the iron ore sample to be tested and sieve it to obtain the core ore material; the particle size of the core ore is ≥0.5mm, preferably 0.5~1mm, 1~2mm or 2~3mm, or the core ore of each particle size is mixed according to the particle size composition of the iron ore to be tested. Take the adhering powder of the sintered ore; the adhering powder is prepared with CaO, Fe2O3, SiO2, Al2O3 and MgO, and the particle size of the adhering powder is less than 100 mesh.

[0027] B) Calculate the amount of core ore and adhesive powder added to the sample based on the raw material structure of the sinter;

[0028] The calculation process is as follows: B1) According to the proportion of each raw material in the raw material structure of the mixture B i Nuclear ore content P 核i Adhesive powder content P 粉i Calculate the mass fraction Q of the nucleus ore in the blend. 混核 The mass fraction of the adhesive powder Q 混粉 The mass fraction of each component in the mixture and the mass fraction of each component in the adhesive powder are calculated using the following formulas:

[0029] Q 混核 =∑P 核i ×B i ;

[0030] Q 混粉 =1-Q 混核 ;

[0031] Among them, B i The proportions of each raw material in the mixture, in wt%; P 核i The proportion of each raw material core ore in the blend, in wt%; P 粉i This refers to the content of adhesive powder in each raw material in the mixture;

[0032] B2) Using analytical grade CaO and analytical grade MgO as fluxes, the mixing ratio of the two fluxes is adjusted according to the raw material ratio in the sinter, based on the target basicity of the sinter and the target MgO content. CaO and B MgO Until the following two requirements are met:

[0033] Target alkalinity = (ωCaO)混 ×B 混 +ω CaO ×B CaO ) / (ωSiO 2混 ×B 混 );

[0034] MgO 含量 =ωMgO 混 ×B 混 +ω MgO ×B MgO ;

[0035] Where, ω CaO To analyze the CaO content in pure CaO; ω MgO To analyze the MgO content in pure MgO; ωCaO 混 B represents the mass fraction of CaO in the mixed material. CaO The proportion of CaO added to the sintering material; ωSiO 2混 The mass fraction of SiO2 in the homogenized material; ωMgO 混 B represents the mass fraction of MgO in the mixed material. MgO The proportion of CaO added to the sintering material; MgO 含量 Target MgO content in sinter; B 混 B represents the proportion of the homogenized material in the sintering material. 混 =1-B CaO -B MgO ;

[0036] Calculate the mass fraction Q of the nuclear ore in the sinter. 烧核 The mass fraction of the adhesive powder Q 烧粉 :

[0037] Q 烧核 =Q 混核 ×B 混 ;

[0038] Q 烧粉 =1-Q 烧核 ;

[0039] Among them, Q 烧核 Q represents the mass fraction of the core ore in the sinter; 混核 B represents the mass fraction of the core ore in the blended material. 混 The proportion of the homogenized material in the sintering material; Q 烧粉 The mass fraction of the adhering powder in the sintering material;

[0040] Calculate the mass fraction of each component in the adhesive powder of the sintered material;

[0041] B3) Calculate the amount of nuclear ore added to the sample W according to the total mass of the nuclear ore and the adhesive powder in a single experiment as n grams. 核Adhesive powder dosage W 粉 The amount of each analytical grade reagent added to the sample is calculated based on the mass fraction of each component in the adhesive powder calculated according to the sintering batch. The calculation formula is as follows:

[0042] W 核 =n×Q 烧核 ;

[0043] W 粉 =n×Q 烧粉 ;

[0044] W i =W 粉 ×ω i ;

[0045] Where, ω i W represents the mass fraction of each component of the adhesive powder in the sample. i W represents the amount of each component of the adhesive powder added to the sample. 核 W represents the amount of nuclear ore added to the sample. 粉 Q represents the amount of adhesive powder added to the sample. 烧核 Q represents the mass fraction of the core ore in the sinter; 烧粉 This represents the mass fraction of the adhering powder in the sintering material.

[0046] C) Mix the nuclear ore and adhesive powder into a mixed powder according to the calculated dosage, and then press the mixed powder into a pressed sample;

[0047] D) The pressed sample is subjected to a calcination experiment, and the weight M0 of the calcined sample is weighed. The calcination experiment process is as follows: the temperature is raised to 600℃ in 4 hours, then raised to 1000℃ in 1.5 hours; then raised to 1280℃ in 3.5 hours and held for 4 hours; then cooled to 1000℃ in 3 hours, and finally cooled naturally.

[0048] E) The roasted sample was subjected to a drum test. After drum test, the sample was sieved and weighed. The mass of the sample with >5mm was recorded as M1 and the mass of the sample with <1mm was recorded as M2. The drum test process was as follows: the drum speed was 50±2r / min.

[0049] F) The consolidation strength and pulverization rate of iron ore are calculated using the following formula:

[0050] Consolidation strength = M1 / M0 × 100%;

[0051] Powdering rate = M2 / M0 × 100%.

[0052] 3) Calculation of core ore composition: The core ore refers to the iron ore of different particle sizes that play different roles during the mixing and granulation of raw materials in the sintering process. Particles ≥0.5mm act as core ore, that is, the core in the middle of the quasi-particles; particles <0.5mm act as adhesive powder, adhering to the core ore to form quasi-particles.

[0053] 3.1) According to the proportions of each raw material in the benchmark ore blending scheme, B i The content of P in each raw material ore i Calculate the mass fraction Q of the nucleus ore in the mixture. 核 The core ore content refers to the mass fraction of the iron ore of this variety with a particle size of ≥0.5mm, and the calculation formula is as follows (Ⅰ);

[0054] Q 核 =∑P i ×B i , ∑B i =1 (Ⅰ);

[0055] 3.2) According to the proportions B of each raw material in the benchmark ore blending scheme. i The content of P in each raw material ore 核i Calculate the content A of this raw material in the nuclear ore. i The calculation formula is as follows (II):

[0056] A i =P 核i ×B i / Q 核 ,∑A i =1(Ⅱ).

[0057] 3.3) According to the proportions of each raw material in the proposed adjusted ore blending scheme, B i The content of P in each raw material ore i Calculate the mass fraction Q of the nucleus ore in the mixture. 核 The calculation formula is as shown in equation (Ⅰ) above;

[0058] 3.4) According to the proportions of each raw material in the proposed adjusted ore blending scheme, B i The content of P in each raw material ore 核i Calculate the content A of this raw material in the nuclear ore. i The calculation formula is as shown in formula (Ⅱ) above;

[0059] In equations (I) and (II), B i The proportions of each raw material in the ore blending scheme, in wt%; P i The content of nuclear ore in each raw material, in wt%; Q 核 P represents the mass fraction of core ore in the blended material of the ore blending scheme, in wt%. 核i The content of nuclear ore in each raw material, wt%; Ai The content of this raw material in the nuclear ore is expressed in wt%; the ore blending scheme is a benchmark ore blending scheme or a proposed adjusted ore blending scheme.

[0060] 4) Calculation of overall consolidation strength and overall pulverization rate of the ore blending structure: The overall consolidation strength and overall pulverization rate of the raw material structure of the benchmark ore blending scheme and the raw material structure of the proposed adjusted ore blending scheme are calculated respectively. The calculation formulas are as follows: (III) and (IV):

[0061] Overall consolidation strength = ∑G i ×A i (III);

[0062] Overall pulverization rate = ∑F i ×A i (Ⅳ);

[0063] In equations (III) and (IV), G i The consolidation strength of each raw material, %; F i Powdering rate of each raw material, %; A i The content of this raw material in the nuclear ore, in wt%.

[0064] 5) Taking into account the differences in the overall consolidation strength and overall pulverization rate of the raw material structure of the benchmark ore blending scheme calculated in step 4) and the raw material structure of the proposed ore blending scheme, determine the ore blending structure or adjust the ore blending structure again.

[0065] Example: The optimized ore blending method based on the consolidation capacity of coarse-grained iron ore is described in detail below.

[0066] 1) Adjustment of sintering ore blending scheme:

[0067] Table 1 shows the sintering ore blending scheme. The baseline ore blending scheme consists of three types of coarse iron ore and one type of fine iron concentrate. The proposed adjustment scheme #1 uses iron ore OD to replace iron ore OC, while reducing the proportion of iron concentrate OF and increasing the proportion of iron ore OA. The proposed adjustment scheme #2 is based on the proposed adjustment scheme #1, using iron ore OE to replace iron ore OB. There are a total of three ore blending schemes.

[0068] Table 1: Sintering Ore Blending Scheme for Examples (wt%)

[0069]

[0070] 2) Determination of iron ore consolidation capacity:

[0071] Determination of iron ore consolidation capacity under the benchmark ore blending scheme: Based on the raw material structure of the benchmark ore blending scheme, the consolidation capacity of the coarse-grained iron ore of the scheme was determined. The consolidation strength and pulverization rate of each type of coarse-grained iron ore were measured. The results are shown in Table 2.

[0072] Determination of iron ore consolidation capacity under the proposed adjusted ore blending scheme: Based on the raw material structure of the proposed adjusted ore blending scheme, the consolidation capacity of the coarse-grained iron ore under this scheme was determined. The consolidation strength and pulverization rate of each type of coarse-grained iron ore were measured. The results are shown in Table 2.

[0073] Table 2: Iron ore consolidation strength and pulverization rate for each ore blending scheme

[0074]

[0075]

[0076] 3) Calculation of nuclear ore composition:

[0077] 3.1) According to the proportions of each raw material in the benchmark ore blending scheme, B i The content of P in each raw material ore i Calculate the mass fraction Q of the nucleus ore in the blend. 核 Table 3 shows the content of each raw material ore.

[0078] Table 3: Raw material ore content (wt%)

[0079]

[0080] Calculate Q using equation (Ⅰ): 核 =∑P i ×B i =0.7078×0.1416+0.902×0.4383+0.6629×0.2601=0.668.

[0081] 3.2) Calculate the composition of the nuclear ore: According to the proportion of each raw material in the benchmark ore blending scheme B i The content of P in each raw material ore 核i Calculate the content A of this raw material in the nuclear ore. i The calculation is performed using formula (II), and the calculation process is as follows:

[0082] A OA =P 核i ×B i / Q 核 =0.7078 × 0.1416 / 0.668 = 0.15;

[0083] A OB =0.902 × 0.4383 / 0.668 = 0.5918;

[0084] A OC =0.6629×0.2601 / 0.668=0.2581.

[0085] 3.3) Calculate the composition of the core ore in the proposed adjusted ore blending scheme using formulas (Ⅰ) and (Ⅱ), that is, the content A of the raw material in the core ore of the proposed adjusted ore blending scheme. i The results are shown in Table 4;

[0086] Table 4: Core Ore Composition for Each Ore Blending Scheme

[0087]

[0088] 4) Calculation of overall consolidation strength and overall pulverization rate of the ore blending structure:

[0089] Equations (III) and (IV) are used to calculate the overall consolidation strength and overall pulverization rate of the benchmark ore blending structure and the proposed adjusted ore blending structure, respectively. Taking the benchmark ore blending structure as an example, the calculation process is as follows:

[0090] Overall consolidation strength of the benchmark ore blending structure = ∑G i ×A i =97.42×0.15+86.13×0.5918+74.31×0.2581=84.76;

[0091] The overall pulverization rate of the benchmark ore blending structure = ∑Fi×Ai = 2.11×0.15 + 10.04×0.5918 + 19.79×0.2581 = 11.36.

[0092] The calculation results for each ore blending scheme are shown in Table 5.

[0093] Table 5: Overall Consolidation Strength and Pulverization Rate of Each Ore Blending Scheme

[0094]

[0095] 5) Optimization of ore blending structure:

[0096] The overall consolidation strength of the proposed ore blending scheme #1 is 86.21%, which is 1.45% higher than the benchmark scheme, and the overall pulverization rate is also lower than the benchmark scheme. The overall consolidation strength of the proposed ore blending scheme #2 is lower, and the pulverization rate is higher, which is not conducive to improving sintering indicators. Therefore, the proposed ore blending scheme #1 can be used to adjust the raw material structure in production.

[0097] 6) Effect verification:

[0098] The above three schemes were verified by sintering cup test. After sintering, the drum strength and yield of sintered ore were measured. The results of the sintered ore performance test are shown in Table 6.

[0099] Table 6: Sinter properties and sintering parameters for each ore blending scheme

[0100]

[0101] Results: As shown in Table 6, compared with the baseline ore blending scheme, the drum strength and yield of the proposed ore blending scheme #1 are improved, while the drum strength and yield of the proposed ore blending scheme #2 are reduced, which is consistent with the evaluation conclusion. Therefore, the consolidation capacity of coarse-grained iron ore and the composition of the core ore can effectively reflect the correspondence between the sintering performance of a single type of iron ore and the overall ore blending structure performance. Based on this, a quantitative evaluation of sinter quality indicators can be achieved. Under the current severe steel industry situation, this can help enterprises establish a rapid and accurate method for evaluating iron ore sintering performance and optimizing ore blending structure, thus achieving the rational utilization of resources.

Claims

1. An optimized ore blending method based on the consolidation capacity of coarse-grained iron ore, characterized in that, The following steps are included: 1) The original ore blending scheme is used as the baseline ore blending scheme, and the ore blending scheme to be adjusted is the proposed adjusted ore blending scheme; 2) Based on the raw material structure of the benchmark blending scheme, the consolidation capacity of the coarse-grained iron ore in this scheme was determined, and the consolidation strength and pulverization rate of each type of coarse-grained iron ore were measured. Based on the raw material structure of the proposed adjusted blending scheme, the consolidation capacity of the coarse-grained iron ore in this scheme was determined, and the consolidation strength and pulverization rate of each type of coarse-grained iron ore were measured. The determination process for the consolidation strength and pulverization rate is as follows: A) Take the iron ore sample to be tested and sieve it to obtain the core ore material; the particle size of the core ore is ≥0.5mm, or the core ore of each particle size is mixed according to the particle size composition of the iron ore to be tested; take the adhesive powder of the sintered ore; the adhesive powder is prepared with CaO, Fe2O3, SiO2, Al2O3 and MgO, and the particle size of the adhesive powder is less than 100 mesh; B) Calculate the amount of core ore and adhesive powder added to the sample based on the raw material structure of the sinter; The calculation process is as follows: B1) According to the proportion of each raw material in the raw material structure of the mixture B i Nuclear ore content P 核i Adhesive powder content P 粉i Calculate the mass fraction Q of the nucleus ore in the blend. 混核 The mass fraction of the adhesive powder Q 混粉 The mass fraction of each component in the mixture and the mass fraction of each component in the adhesive powder are calculated using the following formulas: Q 混核 =∑P 核i ×B i ; Q 混粉 =1-Q 混核 ; Among them, B i The proportions of each raw material in the homogenized mixture are given in wt%; P 核i The proportions of each raw material core ore in the blend, in wt%; P 粉i This refers to the content of adhesive powder in each raw material in the mixture; B2) Using analytical grade CaO and analytical grade MgO as fluxes, the mixing ratio of the two fluxes is calculated according to the raw material ratio in the sinter, and adjusted based on the target basicity and target MgO content of the sinter. CaO and B MgO until the following two requirements are met: Target alkalinity = (ωCaO) 混 ×B 混 +ω CaO ×B CaO ) / (ωSiO 2混 ×B 混 ); MgO 含量 =ωMgO 混 ×B 混 +ω MgO ×B MgO ; Where, ω CaO To analyze the CaO content in pure CaO; ω MgO To analyze the MgO content in pure MgO; ωCaO 混 B represents the mass fraction of CaO in the mixed material. CaO The proportion of CaO added to the sintering material; ωSiO 2混 The mass fraction of SiO2 in the homogenized material; ωMgO 混 B represents the mass fraction of MgO in the mixed material. MgO The proportion of CaO added to the sintering material; MgO 含量 Target MgO content in sinter; B 混 B represents the proportion of the homogenized material in the sintering material. 混 =1-B CaO -B MgO ; Calculate the mass fraction Q of the nuclear ore in the sinter. 烧核 The mass fraction of the adhesive powder Q 烧粉 : Q 烧核 =Q 混核 ×B 混 ; Q 烧粉 =1-Q 烧核 ; Among them, Q 烧核 Q represents the mass fraction of the core ore in the sinter; 混核 B represents the mass fraction of the core ore in the blended material. 混 The proportion of the homogenized material in the sintering material; Q 烧粉 The mass fraction of the adhering powder in the sintering material; Calculate the mass fraction of each component in the adhesive powder of the sintered material; B3) Calculate the amount of nuclear ore added to the sample W according to the total mass of the nuclear ore and the adhesive powder in a single experiment as n grams. 核 Adhesive powder dosage W 粉 The amount of each analytical grade reagent added to the sample is calculated based on the mass fraction of each component in the adhesive powder calculated according to the sintering batch. The calculation formula is as follows: IN 核 =n×Q 烧核 ; IN 粉 =n×Q 烧粉 ; IN i =W 粉 ×ω i ; Where, ω i W represents the mass fraction of each component of the adhesive powder in the sample. i W represents the amount of each component of the adhesive powder added to the sample. 核 W represents the amount of nuclear ore added to the sample. 粉 Q represents the amount of adhesive powder added to the sample. 烧核 Q represents the mass fraction of the core ore in the sinter; 烧粉 The mass fraction of the adhering powder in the sintering material; C) Mix the nuclear ore and adhesive powder into a mixed powder according to the calculated dosage, and then press the mixed powder into a pressed sample; D) The pressed sample was subjected to a calcination experiment, and the weight M0 of the calcined sample was weighed. The calcination experiment process was as follows: the temperature was raised to 600℃ in 4 hours, then raised to 1000℃ in 1.5 hours; then raised to 1280℃ in 3.5 hours and held for 4 hours; then cooled to 1000℃ in 3 hours, and finally cooled naturally. E) The roasted sample was subjected to a drum test. After drum test, the sample was sieved and weighed. The mass of the sample >5mm was recorded as M1 and the mass of the sample <1mm was recorded as M2. The drum test process was as follows: the drum speed was 50±2r / min. F) The consolidation strength and pulverization rate of iron ore are calculated using the following formula: Consolidation strength = M1 / M0 × 100%; Powdering rate = M2 / M0 × 100%; 3) According to the proportions B of each raw material in the benchmark ore blending scheme and the proposed adjusted ore blending scheme respectively. i The content of P in each raw material ore i Calculate the mass fraction Q of the nuclear ore in the blended material of each scheme. 核 The calculation formula is as follows (Ⅰ); then, according to the proportions B of each raw material in the benchmark ore blending scheme and the proposed adjusted ore blending scheme, respectively... i The content of P in each raw material ore 核i Calculate the content A of this raw material in the nuclear ore of each scheme. i The calculation formula is as follows (II): Q 核 =∑P i ×B i ,∑B i =1 (Ⅰ); A i =P 核i ×B i / Q 核 ,∑A i =1 (Ⅱ); 4) Calculate the overall consolidation strength and overall pulverization rate of the raw material structure in the benchmark ore blending scheme and the raw material structure in the proposed adjusted ore blending scheme, respectively. The calculation formulas are as follows: (III) and (IV): Overall consolidation strength = ∑G i ×A i (III); Overall pulverization rate = ∑F i ×A i (Ⅳ); 5) Taking into account the differences in the overall consolidation strength and overall pulverization rate between the raw material structure of the benchmark ore blending scheme and the raw material structure of the proposed adjusted ore blending scheme, determine or readjust the ore blending structure. The coarse-grained iron ore is an iron ore variety containing particles of ≥0.5mm.

Citation Information

Patent Citations

  • Ore blending method based on high-temperature metallurgical performance of iron ore powders

    CN110600086A

  • Ore blending structure evaluation method based on granulation quasi-particle sintering behavior

    CN111638155A